The Influence of Institutional and Managerial Ownership on Financial Distress with Total Debt to Asset Ratio as a Moderating Variable - Atika Syuliswati; Andi Asdani; Riezky Amalia (Politeknik Negeri Malang, 2023)
Literature regarding bankruptcy prediction illustrates that the variables that are often used as predictors of bankruptcy can be grouped into four. These four things are financial ratios (including company and market characteristics), macroeconomic variables, corporate governance, and other special variables. The aim of this research is to determine whether there is an influence of institutional ownership on financial distress, managerial ownership on financial distress, the total debt to asset ratio mediates the influence of institutional ownership on financial distress, the total debt to asset ratio mediates the influence of managerial ownership on financial distress. The object of this research is property and real estate companies listed on the Indonesia Stock Exchange (BEI) between 2017 and 2021. The sample consists of 32 companies. The analysis used is multiple linear analysis using the partial least squares program. The results show that institutional ownership has no significant effect on financial distress, managerial ownership has no significant effect on financial distress, total debt to asset ratio does not mediate the effect of institutional ownership on financial distress, total debt to asset ratio does not mediate the effect of managerial ownership on financial distress.